A Critical Discourse Analysis of Manipulation in Theresa May’s Speech on Brexit - Kadhim, Riyadh Tariq; Jawad, Sa’id Abdulwahab (International Journal of Psychosocial Rehabilitation, 2020)
This paper conducts a critical discourse analysis of manipulation in the speech of Theresa May, the former Prime Minister of UK, concerning Brexit negotiations presented in UK House of Commons on October 25, 2018. The major aims of this study are: (1) Identifying the strategies the speaker employs to convey certain manipulative messages; (2) Identifying the impact of the respective ideology of the political speaker in discursively manipulating information and fact dissemination to the audience; (3) Examining aspects of focus on particular layers of words and meanings such as nouns, verbs, adjectives, and adverbs in addition to rhetorical devices to help understanding manipulation in the selected political speech; (4) Pinpointing the syntactic structures May makes use of in manipulating Members of Parliament in the House of Commons; (5) Figuring out how speech act categories participate in the construction of manipulation.